A profissionalização do campo do desenvolvimento rural na região do Sisal - Mendonça, Patrícia Maria Emerenciano de (2009)
This study aims at verifying the existence of the professional field of rural development in the Sisal Region, in Bahia’s semi-arid region, analyzing the forms through which this process might have contributed to the institutionalization of ideas on what rural development entails and how it might have opened space for the creation of new local logics. As to methodological approaches, micro and macro social analyses were integrated, having the concept of social field as analytical level so as to deal with middle range theories in order to explain social phenomena, particularly neo-institutional and social movement theories. Empirical survey was based on primary data collected in different periods from interviews and observations, to which were added a considerable amount of secondary data gathered from reports, newsletters, videos, newspapers and other academic works. In order to historically recover the field of rural development, from the 70’s to the present days, discourse analysis technique was employed, so as to characterize actors, their main logics of action, particularly those related to professionalization. The attempt at conceptualizing professionalization and clarifying what is being considered as the field or rural development were an important task of the work. Four main contrasting forces in the field, influencing its professionalization were identified: Insurgent Solidarity; insurgent solidarity and economic insertion conflicts; particular forms of relation between State and society; and the insertion of themes and practices absorbed during actors/fields mimetic, regulative and normative mechanisms at micro and macro levels. From the identification and analysis of forces involved in professionalization in the field, suggestions are put forward as to the enlargement of the understanding on professionalization and institutional entrepreneurship, which might be relevant to future studies aiming at integrating agency-structure analyses and individual and collective action dimensions.